A case study on accounting faculty's perceptions of technology in accounting classes. (4th July 2019) - Brands, Kristine M.; Elam, Debora A.
The accounting profession is undergoing a transformation because of the explosion of the amount of financial data and information available to organisations, the demand for real-time access to information and the use of business analytics. The accountants of the future need to be qualified to address these challenges. This means that higher education accounting degree programs must adapt their curriculums and courses to leverage technology tools and practices to ensure that their accounting faculties are prepared to teach these courses. The purpose of this exploratory descriptive case study was to evaluate accounting instructors' perceptions and experiences with technology to identify best practices to develop their technological intelligence to enable them to implement technology into accounting programs and courses to meet the demands that technology is placing on the accounting profession.